PENGARUH LATIHAN PASSING SEGI EMPAT TERHADAP TEKNIK DASAR PASSING SISWA PUTRA DI SEKOLAH SEPAK BOLA KSATRIA SOLO USIA 10-12 TAHUN - Muhammad Diaz Priambodo; Karlina Dwijayanti; Widha Srianto (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2023)
This study aims to determine the effect of rectangular passing practice on the ability of basic passing techniques of athletes at the Solo Knights Soccer School aged 10-12 years. The type of research used in this research is to use the design "The One Group Pretest Post-test Design". The population of the study was the students of the Solo Knights Soccer School aged 10-12 years. Meanwhile, the research sample was 20 students. The instrument to be used is a soccer skill test in the form of a "low passing to target" test. The data analysis technique in this study used quantitative data analysis. The hypothesis was tested using a t-test with the help of the SPSS 25 program, namely by comparing the mean between group 1 (pretest) and group 2 (post-test). Based on the results of the research the Effect of Quadrilateral Passing Practice on the Basic Passing Techniques of Male Students at the Solo Knights Soccer School Ages 10-12 Years. Researchers obtained data from paired sample t test results, namely the value of Sig. (2-tailed) 0.00 < 0.05 so Ha was rejected which was then analyzed so that it was concluded that giving rectangular training treatment had a significant effect on increasing the Passing ability of SSB Ksatria Solo students aged 10-12 years.